Breach of human rights by nigerian police in the performance of its functions: need for a reform (2013)
Nigerian Police is charged with the responsibility of upholding the law and ensuring order is kept within the polity. It is however observed that the police in carrying out its functions constantly abuses the rights of the citizens which are considered as natural rights and very fundamental to every human existence. This study aims at examining the roles of the police in Nigeria and the various ways and the rights of citizens are being encroached upon by the said police. The legal standards prescribed for the operations of Nigerian police are measured against the international standards as a parameter in order to determine the weak points of the Nigerian standards. Suggestions are therefore made on how Nigerian police can be more humane in carrying out its functions.